Oocyte dimensions of dominant subtropical sea urchins in the Northeast Atlantic Ocean (June 2020–May 2021) - Raibel Núñez-González; Airam Nauzet Sarmiento-Lezcano; Ekin Tilic; Maria Jose Caballero Cansino; J J Castro Hernández (PANGAEA, 2025)
Biometric and reproductive data of three sea urchin common species, Paracentrotus lividus, Arbacia lixula, and Sphaerechinus granularis, in the Central-Eastern Atlantic extquotesingles rocky shores were collected over a one-year sampling period, from June 2020 to May 2021, in different localities of Gran Canaria Island. The datasets include biometric measurements such as test diameter, height, total wet weight, gut weight, and gonad weight, along with reproductive data including sex and maturity stage for each individual sampled at the different localities. In addition, oocytes from mature females of each species were measured to compare the size between species. The collected specimens were identified in the laboratory to the lowest possible taxonomic level, and those selected for sex and sexual maturity analysis were examined following a methodology based on macroscopic observation of the gonads and histological analysis (Byrne, 1990; Lozano et al., 1995). After histological analysis, the ovaries of mature females of three sea urchin common species, Paracentrotus lividus, Arbacia lixula, and Sphaerechinus granularis, on the Central-Eastern Atlantic extquotesingles rocky shores were photographed. The oocytes were measured using ImageJ software (Rueden 2017) to compare the sizes of these cells between species. The dataset includes the diameter of each oocyte measured and the code of each individual.